Toll-like receptors 2 and 4 are differentially involved in Fas dependent apoptosis in Peyer's patch and the liver at an early stage after bile duct ligation in mice. Issue 1 (23rd August 2005) - Ogawa, A; Tagawa, T; Nishimura, H; Yajima, T; Abe, T; Arai, T; Taniguchi, M; Takeda, K; Akira, S; Nimura, Y; Yoshikai, Y
Abstract : Background and aims: Surgical management of extrahepatic cholestasis is frequently complicated by bacterial translocation and severe liver injury. The aim of this study was to clarify the involvement of Toll-like receptors (TLRs) in the pathogenesis of bacterial translocation and liver injury in obstructive cholestasis. Methods: TLR2 deficient (TLR2 −/− ), MyD88 −/−, Jα281 −/−, gld / gld, and lpr / lpr mice, all of which have a C57BL/6 background, and C3H/HeN and TLR4 mutated C3H/HeJ mice were subjected to bile duct ligation (BDL). Faecal IgA and serum alanine aminotransferase levels were determined after BDL. Apoptosis was examined by histological and flow cytometric analyses of cells from Peyer's patches and the liver. Results: The size and number of B cells in Peyer's patches markedly decreased on day 3 after BDL. Increased apoptosis in Peyer's patch B cells was evident on day 1 after BDL in control mice but not in lpr / lpr, MyD88 −/−, or C3H/HeJ mice. On the other hand, TLR2 and Fas ligand expression on intrahepatic NK1.1 + T cells increased on day 1 after BDL in C57BL/6 mice. Liver injury and apoptosis were evident on day 1 after BDL in control and C3H/HeJ mice but were significantly reduced in TLR2 −/−, Jα281 −/−, gld / gld, and lpr / lpr mice. Conclusions: TLR4 and TLR2 may play important roles in Fas dependent apoptosis in Peyer's patch B cells and hepatocytes, respectively, at an early stage after BDL in mice.